Pendidikan Akhlak Pendidikan Akhlak Karimah Berbasis Kultur Pesantren: Indonesia - Muhammad Aditya Firdaus; Rinda fauzian (Universitas Muhammadiyah Prof Dr Hamka, 2020)
The problem with the moral decadence of students is that it important to find a solution. Schools that apply the pesantren culture are seen able to solve it and as an alternative in responding to community anxiety, especially in the issue of immoral behavior. The purpose of this research is to elaborate the design of the pesantren culture, the process of forming the Akhlak Karimah, and the efforts to form the character of the students. The research method used is descriptive method. Data were collected through observation, interview and documentation techniques. The data was taken from SMKT Ad-Dimyati Bandung. The results showed (1) the design of the pesantren culture of SMKT Ad-Dimyati Bandung was visionary and oriented towards the goal of integrating the school curriculum with the pesantren curriculum. (2) The educational process focuses on intellectual and emotional development within the framework of good morals. (3) In instilling a pesantren culture to shape the morals of students, emphasizing all pesantren programs that are oriented towards the vision and mission of the school which give birth to participatory contributions.